Detection of fetal growth retardation : diagnostic agreement between measurement of uterine fundal height with measurement of fetal biometry using ultrasonography - Ricardi W. Alibasjah Ricardi W. Alibasjah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
This study was carried out to evaluate the diagnostic agreement between measurement of uterine fundal height with measurement of fetal biometry detecting intrauterine fetal growth retardation.The study consisted of two phases, i.e. determination of standard of uterine fundal height and a test of the standard against ultrasonography, that was currently regarded the most reliable tool in the detection of intrauterine fetal growth retardation. Data was analyzed using agreement analysis with Kappa statistics and intraclass correlation coefficient.The first phase showed a standard curve for the growth of uterine fundal height at 10th, 50th and 90th percentiles. This curve was constructed from 1,024 measurements of uterine fundal height on 487 pregnant mothers at 24-42 weeks of gestational age visiting antenatal clinics at Dr. Sardjito Hospital, Yogyakarta, from 21 March to 4 June 1992. There was a positive correlation between gestational age and uterine fundal height (r=0.7362, p<0.01). The average gain in uterine fundal height was 0.7 cm per week, with a steep increase at 24th to 36th week of gestational age and a tendency to level-off after that.Agreement of the diagnosis was tested on 85 mothers living in Lendah Subdistrict, Kulon Progo District, who at the time of the study were 24-40 weeks pregnant. Eight mothers were found to have intrauterine growth retarded infants, either using uterine fundal height measurement with under 10th percentile criteria of abnormality, or ultrasonography. There was a perfect agreement between the two in the detection of intrauterine growth retardation (Kappa=1, p<0.001) and an excellent correlation between uterine fundal height measurement and the measurement of fetal biometry (intraclass correlation coefficient = 0.8655).It was concluded that uterine fundal height measurement represented an excellent alternative in the monitoring of fetal growth and the detection of intrauterine fetal growth retardation starting from 24th week of gestational age.Key words: intrauterine fetal growth retardation - uterine fundal height - ultrasonography - agreement analysis